A PROSPECTIVE VALIDATION OF HEART SCORE FOR SUSPECTED ACS PATIENTS AT THE EMERGENCY DEPARTMENT OF A TERTIARY CARE CARDIAC CENTER IN PAKISTAN - Kumar, Rajesh; Kumari, Shueeta; Naqvi, Kahkashan Zehra; Rehman, Wajahat; Wallam, Faizan Abdul Aziz; Memon, Aziz-ur Rehman; Asghar, Naila; Ashok, Arti; Bai, Barkha; Karim, Musa (Journal of Ayub Medical College Abbottabad, 2022)
Background: The HEART score is reported to be a useful tool for the assessment of suspected acute coronary syndrome (ACS) patients, however, data regarding its validity in our population is scarce. Therefore, aim of this study was to evaluate the prognostic utility of the HEART score to predict major adverse cardiac events (MACE) within 6 weeks in patients presenting to emergency department with chest pain. Methods: This prospective observational study included suspected ACS patients presented with chest pain to the emergency department of a tertiary care cardiac center. Inclusion criteria for the study were consecutive adult patients with suspected ACS, patients with definite diagnosis of ACS based on history, electrocardiography (ECG), and cardiac enzymes were excluded from the study. HEART score was calculated and patients with ‰¥7 score were also excluded. MACE over the 6-weeks after discharge were observed. Results: Total of 281 patients were included in this analysis, 191 (68%) were male and mean age was 52.58±10.63 years. Mean HEART score was calculated to be 4.27±1.06 with 70.8% (199) in moderate risk [4-6]. Area under the curve of HEART score for the prediction of 6-weeks MACE was 0.874 [0.827-0.920] with MACE rate of 31.7% vs. 0% for low- and moderate-risk group respectively. Conclusion: HEART score showed good discriminating power for the prediction of 6-weeks MACE. Risk of MACE for the patients with HEART score of 0-3 is very low and such patients can be discharged from ER without extensive cardiac workup with proper follow-up planned.